Nanomechanical probing of the layer/substrate interface of an exfoliated InSe sheet on sapphire - Beardsley, R.P.; Akimov, Andrey V.; Greener, Jake D.G.; Mudd, Gary W.; Sandeep, Sathyan; Kudrynskyi, Zakhar R.; Kovalyuk, Zakhar D.; Patanè, Amalia; Kent, Anthony J. (Nature Publishing Group, 2016)
Van der Waals (vdW) layered crystals and heterostructures have attracted substantial interest for potential applications in a wide range of emerging technologies. An important, but often overlooked, consideration in the development of implementable devices is phonon transport through the structure interfaces. Here we report on the interface properties of exfoliated InSe on a sapphire substrate. We use a picosecond acoustic technique to probe the phonon resonances in the InSe vdW layered crystal. Analysis of the nanomechanics indicates that the InSe is mechanically decoupled from the substrate and thus presents an elastically imperfect interface. A high degree of phonon isolation at the interface points toward applications in thermoelectric devices, or the inclusion of an acoustic transition layer in device design. These findings demonstrate basic properties of layered structures and so illustrate the usefulness of nanomechanical probing in nanolayer/nanolayer or nanolayer/substrate interface tuning in vdW heterostructures.